Pengaruh perputaran modal kerja, pertumbuhan Penjualan dan perputaran persediaan terhadap Profitabilitas pada perusahaan yang terdaftar di Jakarta Islamic Index (JII) tahun 2019-2023 - Fidyah Safitri; Rico Wijaya Z; Arfah Arfah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to determine the effect of working capital turnover, sales growth, and inventory turnover on profitability in companies listed on the Jakarta Islamic Index (JII) for the 2019–2023 period. Profitability is an important indicator for measuring a company's financial performance, and this study was conducted to determine the extent to which operational efficiency affects profit achievement. The research method used was a quantitative approach with a purposive sampling technique. From the total population, 13 companies were selected that met the criteria during the observation period. The data used were secondary data in the form of annual financial reports analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method with the help of WarpPLS 8.0 software. The results showed that sales growth and inventory turnover significantly influenced profitability. This indicates that increased sales and inventory management efficiency can drive increased company profits. However, working capital turnover did not significantly influence profitability. These findings provide implications for management to focus more on strategies to increase sales and inventory efficiency to improve the company's financial performance.